Play fighting at the playground: understanding preschoolers' experiences and perceptions - Veiga, Guida; Rebocho, Carolina; Pomar, Clarinda (Frontiers in Developmental Psychology, 2025)
Despite the well-established benefits of play, a specific type of play, known as play fighting, remains controversial. This study aims to understand children's perspectives about play fighting through semi-structured interviews of 56 preschoolers (aged 4–6 years). A thematic inductive content analysis examined children's views on the characteristics of play fighting, the differences between play fighting and serious fighting, the factors influencing their engagement and enjoyment, and the strategies they use when difficulties arise during play fighting. The findings reveal that preschoolers have a clear understanding of play fighting. They describe it as non-harmful fighting behaviors performed with minimal force in a playful atmosphere, characterized by positive facial expressions, vocalizations, props, and fantasy themes. Children enjoy play fighting because it is fun, physically active, and involves fantasy themes that allow them to feel empowered. Preschoolers also recognize that play fighting differs from serious fighting. While they identify similar behaviors, serious fighting involves less restraint, greater force, and harm. When play fighting escalates, children use self-regulation strategies to manage the situation and return to a playful state. These findings suggest that play fighting is a valuable context for social-emotional learning and development in young children and should not be disregarded as inappropriate or undesirable behavior. Adults should trust that children know how to take the best of play fighting and ensure that they have the right to participate in this critical form of play.